(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The research aims at measuring the extent of the relationship and influence of the indicators of the Core competencies of the audit firms and offices in the Earning Quality of the private banks listed in the Iraq Stock Exchange under audit. The research community represents 38 banks. The sample of the research has been approved only 10 banks continue to issue their financial statements for the period (2007 – 2017), in addition to the audit offices assigned to audit these banks, which amounted to 14 companies and auditing offices. John’s (1999) model revised by Kothari et al., (2005) was adopted to measure the Earning Quality by finding discretionary accruals and non-discretionary accruals, to measure the Core competencies indicators , which are (Knowledge, experience, skill of auditors, assistants, number of assistants, techniques used and development certificates for auditors and assistants) by a survey questionnaire distributed to the auditors concerned with the examination of banks included in the sample of research. The statistical program (SPSS) was adopted for data analysis and access to results, which showed the existence of a positive relationship and effect with significance of the core competence in the quality of profits.